Strategi Pengembangan Tambak Udang Pada Pt. Dua Putra Perkasa Di Desa Linau Kecamatan Maje Kabupaten Kaur - Muhamad Haikal Al Rasyid; Herri Fariadi (Rashid : Journal of Economic, 2026)
The study aims to determine the internal and external factors that influence the development of shrimp farming at PT. Dua Putra Perkasa and analyze the shrimp farming development strategy implemented by PT. Dua Putra Perkasa. The research method used is quantitative descriptive research with a descriptive research type using SWOT analysis (Strength, Weakness, Opportunity, Threat) as well as IFE and EFE analysis methods. The results revealed that the main strength factor is the high availability of capital (score 3.857), the main weakness factor is low promotion (score 1.714) and the total weight score of the internal factor evaluation matrix is 3.07. The main opportunity factor is the high demand for shrimp (score 3.571), the main threat factor is the risk of disease spread (score 1.714) and the total weight score of the external factor evaluation matrix is 2.79.